Glucofriendly couscous usage in diabetes - Leepica Kapoor; Nitin Kapoor; Sanjay Kalra (Journal of the Pakistan Medical Association, 2024)
Couscous, a staple food of Northern Africa and the Middle East, is consumed across the world. Being carbohydrate – rich, it is often forbidden to persons with diabetes. Its social and cultural connotations, however, do not allow absolute avoidance of this dish in real life. This brief article explores various ways of preparing, serving and eating couscous, in a glucofriendly manner. The authors summarize available literature, and suggest culinary tips to reduce glycaemic index and glycaemic load of this foodstuff. Keywords: Adherence, Biopsychosocial model, Culinary diabetology, Diet, Glycemic index, Glycemic load, Nutrition, patient- centered care